2022
DOI: 10.22365/jpsych.2022.072
|View full text |Cite
|
Sign up to set email alerts
|

Substance use during the COVID-19 pandemic: What is really happening?

Abstract: Transcranial magnetic stimulation (TMS) is a non-invasive method of brain stimulation that is receiving increasingly attention for new clinical applications. Through electromagnetic induction cortical activity can be modulated and therapeutic effects can be achieved in a variety of psychiatric and neurological conditions. According to the World Health Organization (WHO) depression is the most disabling disease in the world and 350 million people suffer from depression globally. Major depression is the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…That survey also showed that the logistic regression for generalized anxiety acted as a significant predictor for increased use of nicotine and other substances ( 12 ). This increase could be a reaction to the stress derived from the pandemic situation, as has previously been demonstrated in the outcomes of other studies researches carried out in Europe ( 34 , 35 ) and the United States ( 36 ). Smokers normally use certain drugs such as anxiolytics; there is a well-known close relationship between smoking and psychiatric disorders (a higher proportion of subjects with mental health disorders smoke, when compared to general population).…”
Section: Discussionsupporting
confidence: 62%
“…That survey also showed that the logistic regression for generalized anxiety acted as a significant predictor for increased use of nicotine and other substances ( 12 ). This increase could be a reaction to the stress derived from the pandemic situation, as has previously been demonstrated in the outcomes of other studies researches carried out in Europe ( 34 , 35 ) and the United States ( 36 ). Smokers normally use certain drugs such as anxiolytics; there is a well-known close relationship between smoking and psychiatric disorders (a higher proportion of subjects with mental health disorders smoke, when compared to general population).…”
Section: Discussionsupporting
confidence: 62%
“…First, our findings suggest high proportions of subjects reporting lifetime use of tobacco, alcohol, cannabis, and cocaine. Mellos and Paparrigopoulos ( 2022 ) have already signed an increase in alcohol consumption among people with severe alcohol use and an increase in cannabis, nicotine, and cocaine use. So several social and demographic factors might explain the high frequency of participants using drugs.…”
Section: Discussionmentioning
confidence: 99%
“…So several social and demographic factors might explain the high frequency of participants using drugs. Mellos and Paparrigopoulos ( 2022 ) explained that those with high consumption levels had higher harmful emotionality mechanisms. Layman et al ( 2022 ) suggested an impact of environmental factors which contribute to the odds of drug use among the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a potential can also substantially benefit patients with addiction and substance use disorders (SUDs) [ 15 ]. The COVID-19 pandemic has given rise to novel dynamics of drug abuse and addiction, with traditional trafficking avenues moving online, although such a shift was already underway before the pandemic broke out [ 16 , 17 , 18 ]. It could therefore be concluded that the criminal element itself has been taking advantage of remote interactions and transactions as the pandemic set in, exhibiting a considerable level of adaptability [ 19 ].…”
Section: Methodsmentioning
confidence: 99%